Cenas de dissenso e a empregabilidade de sujeitos trans em organizações : tensionamentos e experimentações no contexto do BDMG - Túlio Cesar Salvan Pagnan (2021)
This research intends to investigate, in its complexity, the configuration of scenes of dissensus from a case analysis. Two events related to the process of implementing policies for hiring and retaining trans people in a specific organization, the Development Bank of the State of Minas Gerais (BDMG), are analyzed in a more detailed way. The research is not interested in evaluating the way in which the organizational policies of trans employability occur, but in identifying the ambiguities, dissensus, tensions and contradictions between the institutional public scene and the conflicting scenes that emerge from the “BDMG Pró-Equity ”, started in August 2016 and the “Trans Visibility Debate Cycle”, held in the same month. We start from the assumption that BDMG sets up institutional and daily public scenes in which different audiences play predetermined scripts and roles, ensuring the most controlled and optimized modes of production and performance. However, in certain moments of suspension and political subjectivity, scripts fail and these public scenes can harbor scenes of dissensus. In those scenes, spatialities and temporalities are redefined so that other corporealities can enunciate their demands and experiences, frustrating expectations and changing forms of legibility. We highlight how these institutional scenes can harbor scenes of experimentation and conflict, setting up a broader and more complex scenario about trans work and employability. From the political perspective of Jacques Rancière (2018, 2019, 2020), the reflections constructed in this research aim to trace the scenes of demands for trans employability policies as scenes of dissensus that interrupt the consensual rationality that explains the events and the relationship between them. The scene of dissensus is also an anti-hierarchical method of approaching and articulating speeches, situations, discourses, events and bodies. The main objective of this research is to show how the institutional scene and the organizational attempts to implement policies of trans employability are intertwined with scenes of dissensus based on BDMG actions. It is revealed that the relationship between the work of breaking politics and the fictional work of the conflictual scene allows us to build a theoretical-methodological approach that reveals the importance of causing a disturbance in the fixed demarcation of disciplines and rules, redefining the limits between what can be said and the what should remain unspeakable; the proper and the improper; the legitimate and the illegitimate. Precisely by introducing new configurations and dispositions on a asymmetrical game, or by playing with the interval between several speeches, the objective is always to displace and fracture the regimes of thought that would define as legitimate certain ways of doing, speaking and seeing from a stable set of skills, quality or properties.